Internal communication in a Higher Education unit: A post-pandemic analysis - Loor Chancay, Jeoconda; Armijos Triviño, Norma Allyson; Santana Estrella, Ronny Enrique (Scripta Mundi, 2024)
This research focuses on an evaluation of the substantial impact of Covid-19 in the field of Internal Communication of a public Higher Education Institution (HEI), as well as an investigation of the post-pandemic effects that persist in the current context. Academic communication suffered a transcendental alteration due to the social distance measures imposed during the health crisis, which demanded an urgent adaptation of educational procedures, institutional management and extracurricular activities, abruptly moving from the in-person modality to the virtual environment. This situation, which transcends the limits of the IES under study, had a significant impact on the academic and communicational field, generating an innovative mutation of the communicational processes and flows, which resulted in improving the perception of internal audiences regarding communication and their sense of belonging to the organization. To carry out this research, it was selected the Faculty of Social Communication Sciences, one of the 19 academic units of the University of Guayaquil, the largest institution in Ecuador in terms of students enrollment. The approach applied is mixed, combining qualitative and quantitative methods, which were complemented with an analysis of the existing literature about the topic in order to provide a complete understanding of the situation and its repercussions in the context of the IES’s Internal Communication in the post-pandemic.
Keywords: Internal communication; post-pandemic; higher education